Rural Watershed Management : The Power of Integration - Darghouth, Salah; Ward, Christopher; Gambarelli, Gretel; Styger, Erika; Roux, Julienne (World Bank, Washington, DC, 2012)
A watershed is an area that supplies water by surface or subsurface flow to a drainage system or body of water. Watersheds vary from a few hectares to thousands of square kilometers. Watershed management (WSM) is the integrated use of land, vegetation, and water in a specific drainage area with the objective of conserving hydrologic services and reducing or avoiding damage downstream or underground. The first generation of WSM projects emphasized engineering and civil works. By the end of the 1980s, the comparative failure of this top-down approach was clear. Since the 1990s, WSM programs have integrated livelihood improvements and poverty reduction objectives with soil and water conservation.